Directly Mailing gFOBT Kits to Previous Responders Being Recalled for Colorectal Cancer Screening Increases Participation. Issue 5 (18th October 2019) - Tinmouth, Jill; Patel, Jigisha; Austin, Peter C; Baxter, Nancy N; Brouwers, Melissa C; Earle, Craig C; Levitt, Cheryl; Lu, Yan; MacKinnon, Marnie; Paszat, Lawrence; Rabeneck, Linda
Abstract: Background: Colorectal cancer (CRC) screening with guaiac fecal occult blood test (gFOBT) reduces CRC-related death. Average risk individuals should be recalled for screening with gFOBT every 2 years in order to maximize effectiveness. However, adherence with repeated testing is often suboptimal. Our aim was to evaluate whether adding a gFOBT kit to a mailed recall letter improves participation compared with a mailed recall letter alone, among previous responders to a mailed invitation. Methods: We conducted a cluster randomized controlled trial, with the primary care provider as the unit of randomization. Eligible patients had completed a gFOBT and tested negative in an earlier pilot study and were now due for recall. The intervention group received a mailed CRC screening recall letter from their primary care provider plus a gFOBT kit ( n = 431) while the control group received a mailed CRC screening mailed recall letter alone ( n = 452). The primary outcome was the uptake of gFOBT or colonoscopy within 6 months. Results: gFOBT uptake was higher in the intervention group (61.3%, n = 264) compared with the control group (50.4%, n = 228) with an absolute difference between the two groups of 10.8% (95% confidence interval [CI]: 1.4 to 20.2%, P = <0.01). Patients in the intervention group were more likely to complete the gFOBT compared with the control group (odds ratio [OR] = 1.4; 95% CI: 1.1 to 1.9). Conclusion: Our findings show that adding gFOBT kits to the mailed recall letter increased participation among persons recalled for screening. Nine gFOBT kits would have to be sent by mail in order to screen one additional person.